2017
DOI: 10.1039/c7cc01126a
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of coconut oil to fatty alcohols in methanol over a hydrothermally prepared Cu/SiO2 catalyst without extraneous hydrogen

Abstract: A novel one-pot approach selects a hydrothermally synthesized Cu/SiO catalyst (consisting of CuO·SiO and Cu surface species) to catalyze the reduction of a series of fatty esters, fatty acids, and coconut oil to fatty alcohols at 240 °C in methanol without extraneous hydrogen, attaining around 85% conversion and 100% selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…The three calcined Cu/SiO 2 samples all showed strong peaks at bindinge nergies (BE) of 935.4 and 942.9 eV,a ssigned to Cu 2p 3/2 and 2p!3d satellite (*) Cu 2+ + (Figure 5a). [22] The peaks at ak inetic energy (KE)o f916.5 eV for calcined Cu/SiO 2 -DPU and Cu/SiO 2 -IM in the Cu LMM spectra (Figure 5b)were also attributedt oCu 2+ + ,inline with the results obtained by using Cu XPS. Meanwhile, the left-shifted peak of calcined Cu/SiO 2 -DPA( BE = 915.8 eV) compared to BE = 916.5 eV was probablyb ecause of the presence of copper www.chemcatchem.org (Cu 2+ + )p hyllosilicate,b yc ontrast the main specieso nC u/SiO 2 -IM andC u/SiO 2 -DPU were CuO nanoparticles.…”
Section: Characterizationo Ft He Three Cu/sio 2 Samplessupporting
confidence: 80%
See 1 more Smart Citation
“…The three calcined Cu/SiO 2 samples all showed strong peaks at bindinge nergies (BE) of 935.4 and 942.9 eV,a ssigned to Cu 2p 3/2 and 2p!3d satellite (*) Cu 2+ + (Figure 5a). [22] The peaks at ak inetic energy (KE)o f916.5 eV for calcined Cu/SiO 2 -DPU and Cu/SiO 2 -IM in the Cu LMM spectra (Figure 5b)were also attributedt oCu 2+ + ,inline with the results obtained by using Cu XPS. Meanwhile, the left-shifted peak of calcined Cu/SiO 2 -DPA( BE = 915.8 eV) compared to BE = 916.5 eV was probablyb ecause of the presence of copper www.chemcatchem.org (Cu 2+ + )p hyllosilicate,b yc ontrast the main specieso nC u/SiO 2 -IM andC u/SiO 2 -DPU were CuO nanoparticles.…”
Section: Characterizationo Ft He Three Cu/sio 2 Samplessupporting
confidence: 80%
“…Cu X‐ray photoelectron spectroscopy (XPS) and Cu LMM analysis were performed to elucidate the chemical states of Cu (Figure and Table S2). The three calcined Cu/SiO 2 samples all showed strong peaks at binding energies (BE) of 935.4 and 942.9 eV, assigned to Cu 2p 3/2 and 2p→3d satellite (*) Cu 2+ (Figure a) . The peaks at a kinetic energy (KE) of 916.5 eV for calcined Cu/SiO 2 ‐DPU and Cu/SiO 2 ‐IM in the Cu LMM spectra (Figure b) were also attributed to Cu 2+ , in line with the results obtained by using Cu XPS.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous Cu catalysts have been mainly applied in C—O bond derived reactions, such as methanol synthesis from CO/CO 2 hydrogenation, [ 165‐169 ] (reverse) water‐gas shift reactions (WGS) [ 170‐171 ] and ester hydrogeantion, [ 172‐173 ] due to their moderate capability for activation of C—O bond and H 2 .…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…Except for metal sulfides and noble metal catalysts, the sulfur-free non-noble metal catalysts are promising in heterogeneous catalysis. It is found that non-noble metals (e.g., Ni, Co, Cu) are active in deoxygenation of fatty acids and natural oil to hydrocarbons [47,134,135]. Santillan-Jimenez et al investigated the continuous catalytic hydrogenation of model compound and algal lipids to fuel-like hydrocarbons using Ni-Al layered double hydroxide [136].…”
Section: Catalytic Hydroprocessing Of Extracted Algal Oilmentioning
confidence: 99%